3D printing of lignin: Challenges, opportunities and roads onward. Issue 6 (11th May 2021) - Ebers, L.‐S.; Arya, Aditi; Bowland, C. C.; Glasser, W. G.; Chmely, S. C.; Naskar, A. K.; Laborie, M.‐P.
Abstract: As the second most abundant biopolymer on earth, and as a resource recently becoming more available in separated and purified form on an industrial scale due to the development of new isolation technologies, lignin has a key role to play in transitioning our material industry towards sustainability. Additive manufacturing (AM), the most efficient‐material processing technology to date, has likewise made great strides to promote sustainable industrial solutions to our needs in engineered products. Bringing lignin research to AM has prompted the emergence of the nascent "lignin 3D printing" field. This review presents the recent state of art of this promising field and highlights its challenges and opportunities. Following a review of the industrial availability, molecular attributes, and associated properties of technical lignins, we review R&D efforts at implementing lignin systems in extrusion‐based and stereolithography (SLA) printing technologies. Doing so underlines the adage of lignin research that "all lignins are not created equal, " and stresses the opportunity nested in this chemical diversity created mostly by differences in isolation conditions to molecularly select and tune the attributes of technical lignin systems towards desirable properties, be it by modification or polymer blending. Considering the AM design process in its entirety, we finally propose onward routes to bring the full potential to this emerging field. We hope that this review can help promote the unique value and overdue industrial role of lignin in sustainable engineered materials and products. Abstract :